(untitled) (Bangladesh Journal of Neurosurgery, 2019)
TORCH infection is associated with Toxoplasmosis, Treponema pallidum, Rubella, Cytomegalovirus (CMV), Herpes simplex virus (HSV), Hepatitis viruses, Human immunodeficiency virus (HIV), and other infections such as varicella andparvovirus B19.Paediatric age group with congenital hydrocephalus present with different presentation and has different etiology associated too. TORCH infection is associated with increase morbidity and mortality in pediatricsmainly in prenatal and infant age groups. Clinical presentation varies with type of infection involved and clinical outcome varies too. We report our experience with the management of 4 patients with hydrocephalus associated with TORCH infection, its presentation, its sequelae and management. Bang. J Neurosurgery 2019; 8(2): 119-124